The glare - Harrison, Margot (Little, Brown and Company, 2022)
Sixteen-year-old Hedda has spent the last ten years living with her mother on an isolated, tech-free ranch, but now she is ready to rejoin the world of "the Glare"--her term for normal life filled with cell phones, tablets, and computers. Her mother's warning not to go "off-kilter" quickly goes by the wayside when she and her rediscovered friends begin playing the real Glare, a first-person shooter game only available on the Dark Web, a game rumored to be cursed--if a player dies thirteen times on the thirteenth level of the game, that player dies in real life. Hedda gets sucked into the game, and rediscovers the truth about its nightmarish reality--the same reality that traumatized her as a child.